Precision‐Guided Stealth Missiles in Biomedicine: Biological Carrier‐Mediated Nanomedicine Hitchhiking Strategy - Yuyan Zhou; Xinyue Wang; Deyu Zhang; Hanxiao Cui; Xiaorong Tian; Wei Du; Zhenghui Yang; Dongling Wan; Zhiwei Qiu; Chao Liu; Zhicheng Yang; Lizhihong Zhang; et al. (Advanced Science)
Abstract Nanodrug delivery systems (NDDS) have demonstrated broad application prospects in disease treatment, prevention, and diagnosis due to several advantages, including functionalization capability, high drug‐loading capacity, drug stability protection, and the enhanced permeability and retention (EPR) effect. However, their clinical translation still faces multiple challenges, including rapid clearance by the reticuloendothelial system (RES), poor targeting specificity, and insufficient efficiency in crossing biological barriers. To address these limitations, researchers have developed the biological carrier‐mediated nanomedicine hitchhiking strategy (BCM‐NHS), which leverages circulating cells, proteins, or bacteria as natural “mobile carriers” to enhance drug delivery. This approach enables nanocarriers to inherit the intrinsic biological properties, endowing them with immune evasion, prolonged circulation, dynamic targeting, biocompatibility, biodegradability, and naturally optimized biological interfaces. Here, a systematic overview of the BCM‐NHS is provided. First, the review delves into the methods of nanoparticles (NPs) binding and immobilization, encompassing both the surface‐attachment‐mediated “backpack” strategy and the encapsulation‐based “Trojan horse” strategy. Second, the classification of biological carriers, including both cell‐based and non‐cell‐based carriers, is elucidated. Third, the physical properties and release mechanisms of these nanomaterials are thoroughly described. Finally, the latest applications of BCM‐NHS in therapeutic and diagnostic contexts across various disease models including tumor, ischemic stroke, and pneumonia are highlighted.